The role of total polysaccharides from Sonchus arvensis L. in the prevention and treatment of colitis via regulation of gut microbiota and metabolites - Ren, Yachao; Hou, Shenghua; Chen, Guoyou; Zhou, Yulong (Frontiers in Pharmacology, 2026)
BackgroundSonchus arvensis L. is a traditional Chinese food and medicine, and the primary plant metabolites are polysaccharides (SAP). In this study, we aimed to investigate the protective effect of SAP in a colitis model and the potential underlying molecular mechanisms.MethodsC57BL/6 mice were randomly assigned to three groups: the negative control, model, and SAP treatment groups. The influence of SAP on ulcerative colitis (UC) was evaluated by water and food intake, body weight change, diarrhea, bloody stool, colon length, histological analysis, disease activity index, and immune parameters. The effects of SAP on the gut microbiota (GM) were investigated using 16S rRNA sequencing. The impact of SAP on metabolites was evaluated using non-targeted metabolomics analysis.ResultsSAP attenuated colitis and modified immune parameters. 16S rRNA sequencing showed that the abundance of Akkermansia, Rikenella, Rikenellaceae_RC9_gut_group, and unidentified_Clostridia_vadinBB60_group in the model mice was remarkably reversed after SAP treatment. The correlation analysis of GM and the metabolites showed that SAP could regulate five metabolites correlated with GM.ConclusionThe protective effect of SAP on the model mice may be related to GM diversity and metabolites.